2005
DOI: 10.4049/jimmunol.174.11.6577
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Atopy Promotes Th2 Responses to Alloantigens and Increases the Incidence and Tempo of Corneal Allograft Rejection

Abstract: A large body of evidence suggests that corneal allograft rejection is mediated by a type 1 Th cell response and that deviation toward type 2 immunity favors graft survival. However, clinical observations indicate that patients with severe ocular allergies have increased risk of corneal allograft rejection. We used a mouse model of atopic conjunctivitis to evaluate the effects of Th2 immune deviation on corneal allograft survival and possible mechanisms of graft rejection. Our results reveal the following novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 23 publications
2
61
1
5
Order By: Relevance
“…24 The results of our study are consistent with these data and show that allergic conjunctivitis, in particular, accelerates corneal allograft rejection. This result is also consistent with the finding by Beauregard et al 20 of an increased rate of corneal graft rejection in their model of chronic postoperative allergic conjunctivitis. What we have …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…24 The results of our study are consistent with these data and show that allergic conjunctivitis, in particular, accelerates corneal allograft rejection. This result is also consistent with the finding by Beauregard et al 20 of an increased rate of corneal graft rejection in their model of chronic postoperative allergic conjunctivitis. What we have …”
Section: Discussionsupporting
confidence: 83%
“…19 However, in a model of normal risk transplantation, accelerated corneal allograft rejection was found in patients with allergic conjunctivitis, and this was attributed to the Th2 bias induced by systemic sensitization with allergen. 20 Our study examines the effect of perioperative allergic ocular inflammation on allograft survival and on the composition of the inflammatory infiltrate during rejection.…”
mentioning
confidence: 99%
“…However, specific animal studies of rejection have demonstrated that the type 2-mediated immune response may be just as injurious to the allograft as a type 1-mediated immune response (3)(4)(5). Based on these findings and the limited data on the role of type 2 cytokines during the pathogenesis of BOS, we hypothesized that the IL-13 biological axis has an important role during BOS.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that this type of allograft accommodation may be, in part, due to a type 2 immune response. However, there is evidence indicating that type 2 immune responses can also promote rejection (3)(4)(5).…”
Section: B Ronchiolitis Obliterans Syndrome (Bos)mentioning
confidence: 99%
“…Using animal models and histology of failed grafts a Th2-mediated mechanism of rejection was suggested. Beauregard et al 33 described the role of Th1 (28) and Th2 cells working together to instigate rejection. Using mouse models of atopic conjunctivitis, they found an enhanced systemic Th2 response to donor corneal cells and a more rapid onset of rejection without the direct infiltration of the host with esoinophils.…”
Section: Discussionmentioning
confidence: 99%